Maternal obesity alters the placental transcriptome in a fetal sex-dependent manner - Kelly, Amy; Chan, Jeannie; Powell, Theresa L.; Cox, Laura A.; Jansson, Thomas; Rosario, Fredrick J. (Frontiers in Cell and Developmental Biology, 2023)
Infants born to obese mothers have an increased risk of developing obesity and metabolic disease in childhood and adulthood. Although the molecular mechanisms linking maternal obesity in pregnancy to the development of metabolic disease in the offspring are poorly understood, evidence suggests that changes in placental function may play a role. Using a mouse model of diet-induced obesity with fetal overgrowth, we performed RNA-Seq analysis at Embryonic day 18.5 to identify genes differentially expressed in the placentas of obese and normal-weight dams (controls). In male placentas, 511 genes were upregulated, and 791 genes were down-regulated in maternal obesity. In female placentas, 722 genes were down-regulated, and 474 genes were upregulated in response to maternal obesity. The top canonical pathway down-regulated in maternal obesity in male placentas was oxidative phosphorylation. In contrast, sirtuin signaling, NF-kB signaling, phosphatidyl inositol, and fatty acid degradation were upregulated. In female placentas, the top canonical pathways down-regulated in maternal obesity were triacylglycerol biosynthesis, glycerophospholipid metabolism, and endocytosis. In contrast, bone morphogenetic protein, TNF, and MAPK signaling were upregulated in the female placentas of the obese group. In agreement with the RNA Seq data, the expression of proteins associated with oxidative phosphorylation was down-regulated in male, but not female, placentas in obese mice. Similar sex-specific changes in the protein expression of mitochondrial complexes were found in placentas collected from obese women delivering LGA babies. In conclusion, maternal obesity with fetal overgrowth differentially regulates the placental transcriptome in male and female placentas, including genes involved in oxidative phosphorylation.